Odpowiedź :
Odpowiedź:
[tex]a)\\\\4x^3-4x^2-x+1=0\\\\4x^2(x-1)-(x-1)=0\\\\(4x^2-1)(x-1)=0\\\\(2x-1)(2x+1)(x-1)=0\\\\2x-1=0\ \ \ \ \vee\ \ \ \ 2x+1=0\ \ \ \ \ \ \vee\ \ \ \ x-1=0\\\\2x=1\ \ /:2\ \ \vee\ \ \ \ 2x=-1\ \ /:2\ \ \vee\ \ \ \ x=1\\\\x=\frac{1}{2}\ \ \ \ \ \ \ \ \ \ \vee\ \ \ \ x=-\frac{1}{2}\ \ \ \ \ \ \ \ \ \ \ \ \vee\ \ \ \ x=1[/tex]
[tex]b)\\\\x^4-31x^2-30x=0\\\\x(x^3-31x-30)=0\\\\x(x^3+x^2-x^2-x-30x-30)=0\\\\x(x^2(x+1)-x(x+1)-30(x+1))=0\\\\x(x+1)(x^2-x-30)=0\\\\x(x+1)(x^2+5x-6x-30)=0\\\\x(x+1)(x(x+5)-6(x+5))=0\\\\x(x+1)(x+5)(x-6)=0\\\\x=0\ \ \ \ \vee\ \ \ \ x+1=0\ \ \ \ \vee\ \ \ \ x+5=0\ \ \ \ \vee\ \ \ \ x-6=0\\\\x=0\ \ \ \ \vee\ \ \ \ x=-1\ \ \ \ \ \ \vee\ \ \ \ x=-5\ \ \ \ \ \ \ \ \vee\ \ \ \ x=6[/tex]
[tex]c)\\\\9x^3-9x^2-x+1=0\\\\9x^2(x-1)-(x-1)=0\\\\(9x^2-1)(x-1)=0\\\\(3x-1)(3x+1)(x-1)=0\\\\3x-1=0\ \ \ \ \ \ \vee\ \ \ \ 3x+1=0\ \ \ \ \ \ \vee\ \ \ \ x-1=0\\\\3x=1\ \ /:3\ \ \ \ \vee\ \ \ \ 3x=-1\ \ \ \ \ \ \ \ \vee\ \ \ \ x=1\\\\x=\frac{1}{3}\ \ \ \ \ \ \ \ \ \ \ \ \vee\ \ \ \ x=-\frac{1}{3}\ \ \ \ \ \ \ \ \ \ \ \vee\ \ \ \ x=1[/tex]
[tex]d)\\\\x^4-21x^2-20x=0\\\\x(x^3-21x-20)=0\\\\x(x^3+x^2-x^2-x-20x-20)=0\\\\x(x^2(x+1)-x(x+1)-20(x+1))=0\\\\x(x+1)(x^2-x-20)=0\\\\x(x+1)(x^2+4x-5x-20)=0\\\\x(x+1)(x(x+4)-5(x+4))=0\\\\x(x+1)(x+4)(x-5)=0\\\\x=0\ \ \ \ \vee\ \ \ \ x+1=0\ \ \ \ \vee\ \ \ \ x+4=0\ \ \ \ \vee\ \ \ \ x-5=0\\\\x=0\ \ \ \ \vee\ \ \ \ x=-1\ \ \ \ \ \ \vee\ \ \ \ x=-4\ \ \ \ \ \ \ \ \vee\ \ \ \ x=5[/tex]